Body Image Perception, Eating Habits, and Nutritional Status of Female University Students: A Case of Makerere University, Uganda - Bridget Ainembabazi; Agnes Nabubuya; Ivan Muzira Mukisa (Journal of Nutrition and Metabolism)
Conclusion: A big proportion of female students expressed dissatisfaction with their body image despite majority having normal weight status. Targeted mental health programs should be designed to help students deal with dissatisfaction and promote general wellbeing.